Penentu Harga Saham: Analisis Perbandingan Sebelum dan Sesudah Restrukturisasi Hutang Perusahaan - Elok Lailia Kumala; Supami Wahyu Setiyowati; Susmita Dian Indraswari (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2023)
This study aims to determine the effect of liquidity, leverage, profitability on stock prices before and after debt restructuring in non-financial companies IDX-IC listed on the Indonesia Stock Exchange. This research uses quantitative research methods. The population used in this study is a sectoral non-financial company IDX-IC listed on the Indonesia Stock Exchange with a 6-year observation year, namely 2016-2021. The research sample is a company that has carried out debt restructuring from 2017 to 2020, namely 30 companies selected by purposive sampling. Data collection techniques use secondary data. Data analysis techniques use Partial Least Square (PLS), and Partial Least Square-Multi Group Analysis (PLS-MGA) to see the difference in effect between before and after debt restructuring. The results showed that liquidity has a positive and significant effect on stock prices, leverage has no significant effect on stock prices, and profitability has no significant effect on stock prices. The results also show that there is no significant difference in the effect of the independent variables used in the study on stock prices before and after debt restructuring. Keywords: likuidity, leverage, profitability, stock prices, debt restructuring